2000
DOI: 10.1002/jccs.200000103
|View full text |Cite
|
Sign up to set email alerts
|

The Adsorbate Electron Affinity Dependence of Femtosecond Electron Dynamics at Dielectric/Metal Interfaces

Abstract: The two photon photoemission technique has been utilized to investigate the adsorbate electron affinity dependence of interfacial electron transfer dynamics. The comparison of calculated and experimental results highlight a brief discussion of a dielectric continuum model. For the n-heptane/Ag(lll) and the benzene/ Ag(lll) interfaces, the model effectively reproduces experimental image potential state properties. The model fails to adequately describe the influence of anthracene adsorbates on image potential s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Harris and co-workers recently carried out 2PPE studies of Ag(111) adsorbed with a series of aromatic molecules with increasing electron affinity: benzene, naphthalene, and anthracene. 16 However, these experiments did not reveal any molecular resonance. Instead, the authors showed the sensitivity of image states to the presence of molecular layers, depending on the energetics of image states relative to molecular bands.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Harris and co-workers recently carried out 2PPE studies of Ag(111) adsorbed with a series of aromatic molecules with increasing electron affinity: benzene, naphthalene, and anthracene. 16 However, these experiments did not reveal any molecular resonance. Instead, the authors showed the sensitivity of image states to the presence of molecular layers, depending on the energetics of image states relative to molecular bands.…”
Section: Introductionmentioning
confidence: 76%
“…Will such a molecular resonance show free electron like dispersion parallel to the surface as is observed for modified image states? Harris and co-workers recently carried out 2PPE studies of Ag(111) adsorbed with a series of aromatic molecules with increasing electron affinity: benzene, naphthalene, and anthracene . However, these experiments did not reveal any molecular resonance.…”
Section: Introductionmentioning
confidence: 99%
“…10,19,20 The dielectric continuum model, however, does not reproduce the experimental findings for naphthalene and anthracene on Ag(111). 21 An alternative description of the adsorbate electronic structure, based on the two-band nearly free electron model, has successfully reproduced the primary experimental results. Analysis of the calculation provides an explanation for experimental findings, as well as the failure of the dielectric continuum model.…”
Section: Introductionmentioning
confidence: 83%
“…The primary experimental trends seen in the present study have been successfully accounted for with theoretical model calculations. Dielectric continuum descriptions of adsorbate electronic structure have been successful in explaining the influence of numerous adsorbates on image potential states. ,, The dielectric continuum model, however, does not reproduce the experimental findings for naphthalene and anthracene on Ag(111) . An alternative description of the adsorbate electronic structure, based on the two-band nearly free electron model, has successfully reproduced the primary experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorbates with negative electron affinities should from a barrier that pushes the electron away from the surface, increasing its lifetime. This model has been successfully used to explain the IPS energetic positioning and lifetime for several adsorbate systems including noble gasses 22,23 , linear acenes 24 , and alkanes 21,25 . This model, however, also has several inadequacies.…”
Section: Image Potential Statesmentioning
confidence: 99%